Practice makes perfect: effects of mere rehearsal on lay judgments of confessions - Alceste, Fabiana (Psychology, crime & law, 2024)
Informed by individuals wrongfully convicted by confession, and in light of basic research on practice effects on performance, two studies examined the effects of rehearsal on suspects and observers. In Study 1 (N = 37), participants who were guilty or innocent of a mock crime were incentivized to confess and then improve upon that confession three more times. Overall, guilty suspects’ confessions were longer than those of innocents, rehearsal increased statement length in both conditions, and suspects described their rehearsed confessions as easier to give and more believable, and themselves as less nervous. In Study 2, 161 observers watched a single confession from the first study. Results showed that they did not distinguish between true and false confessions; they were biased toward seeing guilt, substantially over-believing false confessions; and rehearsal exacerbated this latter tendency. In the realm of ‘practice makes perfect’, innocence did not serve as a safeguard.